Ethnobotany of Traditional Medicine Plant Ethnic Chinese in Pemangkat Sub-district, Sambas District - Ribka Sinta Uli Panjaitan; Elvi Rusmiyanto P. W.; Mukarlina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Plants used as medicine are believed to be effective in curing diseases. Traditional Chinese medicine has an influence on the growth of local traditional medicine. Traditional Chinese medicine are still practiced until now. This research aims to know the species and the family of plants used, as well as how the processing and methods of using Chinese ethnic medicinal plant in Pemangkat Sub-district from August to October 2022 in Pemangkat Sub-district. The research uses the participant observation. Selection of respondents using the snowball sampling method, with a total of 15 respondents. Data collection through semi-structured interviews. The results of this research included 28 species of plants from 15 families. The highest frequency sitations values are in kacangma/ginjean (Leonurus artemisia L.) and angkak/rice crops (Oryza sativa L.) with a point of 86%, the highest use value of species is kacangma/ginjean (Leonurus artemisia L.) with a point 0,6. The processing of plants is carried out in the six way, that is boiling, brewing, cooking, mashing, dipping and eating directly. Boiling being the most common processing with a value of 37%. Used medicinal plants in the six way, that is drinking, eating, dripping, washing and sticking. Drinking being the most used with a value of 61%.